Establishing The Effect Of Saving Strategies On Wealth Creation In Uganda - Nuwatuhaire, Benard; Ainomugisha, Andrew (International Journal of Advanced Research and Publications, 2019)
The study was carried out to assess the effect of savings strategies on wealth creation in Uganda. Using both quantitative and qualitative approaches, the study adopted correlational and cross-sectional designs on a sample of 96 respondents. Data analysis was carried out at univariate, bivariate and multivariate. Univariate analysis involved use of percentages and descriptive statistics in particular the mean, bivariate was carried out using correlation and multivariate analysis was carried out using regression. The study found out that savings strategies did not significantly affect wealth creation. The study also found out that gender, education level, working experience, monthly income and family background were statistically positive significant factors affecting wealth creation. It was therefore concluded that whereas savings strategies did not influence wealth creation, five personal savings factors namely, gender, education level, working experience, monthly income and family background did. The study recommended that employers both in private sector and public civil services should enhance the remuneration of employees, the government of Uganda should ensure saving training programme and policy makers should design policies that encourage savings to help people create wealth.
Keywords: Savings; Investment and Wealth Creation